Enhancing treatment compliance in the home management of childhood malaria: The use of a participatory approach in ensuring intervention appropriateness (2004)
The study employs a participatory approach in ensuring intervention appropriateness and compliance with prescribed chloroquine regimen for children perceived to be suffering from malaria. The study showed that tailoring education intervention to the special needs of mothers, health workers, and patent medicine sellers and involving them in the design of interventions are some of the best ways of achieving intervetion effectiveness. It also reveals that treatments with tablets predispose to higher compliance rates than syrups. Public participation in the diagnosis of management problems and proffering of interventions has shifted the role of researchers from interventionists to a supportive role of these populations. This strategy can save cost and ensure the permanence of interventions beyond the lifespan of research